(untitled) (Filologia e Linguística Portuguesa, 2022)
The aim of this paper is to present a to analytically describe the strategies of reference to the subject of 2SG (vossa mercê, você, tu), correlating them with the social relations that underlie them in the written production of Minas Gerais in the 19th and 20th centuries to the Theory of Power and Solidarity thought by Brown and Gilman (1960), to the theoretical-methodological assumptions of Historical Sociolinguistics (HERNÁNDEZ-CAMPOY & SHILLING, 2012), the Variationist Sociolinguistics (WEINREICH, LABOV & HERZOG, 2008 [1968]; LABOV, 1994). We assume as a hypothesis the fact that you are more productive than tu, cf. Lopes et alii (2018), Lopes & Rumeu (2015), Rumeu (2020), in historical samples from the 19th and 20th centuries. Based on the written production of Brazilian editors between the 19th and 20th centuries, we observed that the forms tu and você predominate in symmetrical relationships, which suggests the direction of Brazilian society through the domains of Solidarity (BROWN & GILMAN, 1960), while vossa mercê is limited to ascending asymmetrical relationships (from lower to higher), cf. Lopes & Rumeu (2015).